Impact of audit and feedback with action implementation toolbox on improving ICU pain management: cluster-randomised controlled trial. Issue 12 (1st July 2019) - Roos-Blom, Marie-José; Gude, Wouter T; de Jonge, Evert; Spijkstra, Jan Jaap; van der Veer, Sabine N; Peek, Niels; Dongelmans, Dave A; de Keizer, Nicolette F
Abstract : Background: Audit and feedback (A&F) enjoys widespread use, but often achieves only marginal improvements in care. Providing recipients of A&F with suggested actions to overcome barriers (action implementation toolbox) may increase effectiveness. Objective: To assess the impact of adding an action implementation toolbox to an electronic A&F intervention targeting quality of pain management in intensive care units (ICUs). Trial design: Two-armed cluster-randomised controlled trial. Randomisation was computer generated, with allocation concealment by a researcher, unaffiliated with the study. Investigators were not blinded to the group assignment of an ICU. Participants: Twenty-one Dutch ICUs and patients eligible for pain measurement. Interventions: Feedback-only versus feedback with action implementation toolbox. Outcome: Proportion of patient-shift observations where pain management was adequate; composed by two process (measuring pain at least once per patient in each shift; re-measuring unacceptable pain scores within 1 hour) and two outcome indicators (acceptable pain scores; unacceptable pain scores normalised within 1 hour). Results: 21 ICUs ( feedback-only n=11; feedback-with-toolbox n=10) with a total of 253 530 patient-shift observations were analysed. We found absolute improvement on adequate pain management in the feedback-with-toolbox group (14.8%; 95% CI 14.0% to 15.5%) and the feedback-only group (4.8%; 95% CI 4.2% to 5.5%). Improvement was limited to the two process indicators. The feedback-with-toolbox group achieved larger effects than the feedback-only group both on the composite adequate pain management (p<0.05) and on measuring pain each shift (p<0.001). No important adverse effects have occurred. Conclusion: Feedback with toolbox improved the number of shifts where patients received adequate pain management compared with feedback alone, but only in process and not outcome indicators. Trial registration number: NCT02922101 .